2020
DOI: 10.17755/esosder.638880
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrenci̇leri̇ni̇n Problem Çözmeye Yöneli̇k Yansitici Düşünme Beceri̇leri̇ni̇n Ve Matemati̇k Başarilari Arasindaki̇ İli̇şki̇ni̇n İncelenmesi̇

Abstract: Bu araştırma, ortaokul öğrencilerinin problem çözmeye yönelik yansıtıcı düşünme becerilerini belirlemek ve cinsiyet, sınıf düzeyi ve matematik başarısı değişkenleri bağlamında incelemek amacı ile yapılmıştır. Çalışma, ilişkisel tarama ve nedensel karşılaştırma modeline göre desenlenmiştir. Araştırmanın örneklemini Adana ili merkez ilçelerine bağlı orantısız tabakalı örnekleme yöntemine göre belirlenmiş toplam 266 ortaokul öğrencisi oluşturmuştur. Araştırmada veri toplama aracı olarak kişisel bilgi formu ve pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…They determined that mathematics anxiety did not have as great an impact on mathematics achievement as attitude towards mathematics. Finally, the research conducted by Arslan and İnce (2023) revealed that 8th-grade students' attitudes towards the mathematics lesson have an impact on students' test anxiety. Based on the results of this research, the following recommendations were made:…”
Section: Results On What Direction and Level Students' Mathematics Se...mentioning
confidence: 98%
“…They determined that mathematics anxiety did not have as great an impact on mathematics achievement as attitude towards mathematics. Finally, the research conducted by Arslan and İnce (2023) revealed that 8th-grade students' attitudes towards the mathematics lesson have an impact on students' test anxiety. Based on the results of this research, the following recommendations were made:…”
Section: Results On What Direction and Level Students' Mathematics Se...mentioning
confidence: 98%
“…Kocaman (2017) found a weak positive relationship between mathematical thinking and attitude toward mathematics. Baş (2019) reported that there were moderate positive relationships between the higher-order thinking, reasoning, mathematical thinking, and problem-solving variables. Kocaman Üdüm (2021) concluded that there was a moderate positive relationship between mathematical problem-solving skills and logical thinking.…”
Section: Discussion Regarding the Second Research Questionmentioning
confidence: 99%
“…Bu etkili öğrenmeler sayesinde kişi yansıtıcı düşünme becerisini ortaya koyarak problem çözme sürecinde daha etkin rol alır. Yansıtıcı düşünmenin problem çözme sürecindeki önemi dikkate alındığında, ilgili becerinin, en iyi, problem çözme sürecinde gözlenebileceği söylenebilir (Baş, 2013). Yansıtıcı düşünme, bir problem varlığında ortaya çıktığından ve en iyi problem çözme sürecinde gözlenebileceğinden matematik dersi söz konusu olduğunda yansıtıcı düşünme kavramı problem çözmeye yönelik yansıtıcı düşünme olarak düşünülebilir (Shermis, 1992).…”
Section: Introductionunclassified